A Sustainable Approach to Tourism Development in Rural Areas: The Example of Poland - Widawski, Krzysztof; Krzemińska, Alicja; Zaręba, Anna; Dzikowska, Anna (Agriculture (Basel), 2023)
The research presented in this article concerns the issue of rural tourism, which is associated with significant economic and landscape changes in the countryside. It is important that tourist development in these areas be subject to the principles of sustainable development, which are important for the preservation of the environment in which tourism operates. The research topic is related to two of the most salient features of rural tourism today, environmental sustainability and pro-environmental behavior, which are considered the right ways to achieve sustainability goals. The main research aim presented is to indicate which of the postulates of sustainable development are being implemented and how concerning the functioning and development of rural tourism is on the Polish tourism market. Another goal is to indicate what types of resources in the rural environment are the basis for the preparation of a tourist product; for whom and how these resources are to be used; as well as the participation of the local community in the management of the resources that constitute its own environment, one of the basic principles of sustainable development. The primary method used was a document analysis and an analysis of selected websites presenting rural environmental resources used in this form of tourism. The research identified that sustainable approaches to tourism development in rural areas in Poland are appropriate with respect to the resources available there and to both natural and cultural values. For resources used in a rural environment, emphasis is placed on the protection of both elements. It has been identified that one idea for their protection is sustainable sharing, which assumes rational use to an extent that would not affect the nature of the assets but at the same time could benefit the local community. Both values are used in different ways but, in addition to their purely recreational value, their educational value is equally important each time.